Correlates of accelerometry non-adherence in an economically disadvantaged minority urban adult population. Issue 8 (August 2020) - Cato, Matthew S.; Wyka, Katarzyna; Ferris, Emily B.; Evenson, Kelly R.; Wen, Fang; Dorn, Joan M.; Thorpe, Lorna E.; Huang, Terry T.-K.
Abstract: Objectives: The purpose of this study was to examine socio-demographic and psychosocial correlates of non-adherence to an accelerometry protocol in an economically disadvantaged urban population. Design: Cross-sectional study. Methods: We analyzed 985 New York City adult participants aged 18–81 years from the Physical Activity and Redesigned Community Spaces (PARCS) study. Participants were asked to wear a hip-worn ActiGraph GT3X-BT accelerometer for one week. Adherent accelerometer wear was defined as ≥3 days of ≥8 h/day of wear over a 7-day period and non-adherent accelerometry wear was defined as any wear less than adherent wear from returned accelerometers. Examined correlates of adherence included sociodemographic and psychosocial characteristics (e.g., general physical/mental health-related quality of life, self-efficacy for exercise, stress, sense of community/neighborhood well-being, and social cohesion). Results: From the total sample, 636 (64.6%) participants provided adherent wear and 349 (35.4%) provided non-adherent wear. In multivariable analysis, younger age (odds ratio [OR] = 0.63, 95% confidence interval [CI]: 0.53–0.75), poorer health-related quality of life (OR = 0.80, 95% CI: 0.65–0.98 for physical health and OR = 0.77, 95% CI: 0.62–0.94 for mental health), lower sense of community (OR = 0.79, 95% CI: 0.62–1.00) and current smoking status (OR = 1.97, 95% CI: 1.35–2.86) were associated with non-adherent wear. Conclusions: Non-adherent wear was associated with younger age, smoking, and lower self-reported physical/mental functioning and sense of community. This information can inform targeted adherence strategies to improve physical activity and sedentary behavior estimates from accelerometry data in future studies involving an urban minority population.